Assessment of burnout rate and related factors in selected wards - Sadeghzadeh Nasseri, marzieh; Ashktorab, tahereh; AtashzadehShoredeh, foroozan; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2015)
Background and Aims: Nurses experience numerous stresses in their work which may cause burnout .The goal of present study was to determine the prevalence and factors associated with burnout in nurses working in selected departments of teaching hospitals of University of Medical Sciences and Health Services in Fasa and Jahrom cities. Materials and Methods: In this cross – sectional study,120 nurses working in teaching hospitals Fasa and Jahrom cities were included. Data were collected by a questionnaire which consisted a demographic information section , the Copenhagen Burnout Inventory (CBI) and a list factors related to burnout. Internal consistency of the questionnaires were obtained by calculating cronbach alpha which was = 0.7 and =0.76 for "Copenhagen Burnout Inventory" and "related factors with burnout questionnaire " respectively .Test –re test reliability was r=0. 89 and r=0.70 for "Copenhagen Burnout Inventory" and "related factors with burnout questionnaire " respectively. Data was analyzed with SPSS 17 software . Finding: The results showed that the mean scores was for personal-related burnout 52.94 ± 18.35% ,workrelated burnout 54.14 ± 18.64%, the client-related burnout 41.91 ± 19.91 percent. According to the classification made, burnout in the area of personal and work-related burnout among nurses was high level and within client-related burnout was moderate. This study showed that the economic factor was the less important factor for burnout , and the care related factors had the most significant association with burnout in study units. Conclusion: High levels of burnout in this study indicate the need for more attention from managers and resolving the causes of burnout in nurses. Keywords: Burnout, Related factors, Nurse